Cover Image. Issue 4 (12th March 2019) - Levipan, Héctor A.; Irgang, Rute; Tapia‐Cammas, Diana; Avendaño‐Herrera, Ruben
Abstract : The cover image is based on the Short Communication A high‐throughput analysis of biofilm formation by the fish pathogen Tenacibaculum dicentrarchi by Héctor A. Levipan et al., https://doi.org/10.1111/jfd.12949 .